Transcriptomic Changes Induced by Deletion of Transcriptional Regulator GCR2 on Pentose Sugar Metabolism in Saccharomyces cerevisiae - Shin, Minhye; Park, Heeyoung; Kim, Sooah; Oh, Eun Joong; Jeong, Deokyeol; Florencia, Clarissa; Kim, Kyoung Heon; Jin, Yong-Su; Kim, Soo Rin (Frontiers in Bioengineering and Biotechnology, 2021)
Being a microbial host for lignocellulosic biofuel production, Saccharomyces cerevisiae needs to be engineered to express a heterologous xylose pathway; however, it has been challenging to optimize the engineered strain for efficient and rapid fermentation of xylose. Deletion of PHO13 (pho13) has been reported to be a crucial genetic perturbation in improving xylose fermentation. A confirmed mechanism of the pho13-positive effect on xylose fermentation is that the deletion of PHO13 transcriptionally activates the genes in the non-oxidative pentose phosphate pathway (PPP). In the current study, we found a couple of engineered strains that were independent from the pho13-positive effect, among the several others we examined. Genome resequencing of the pho13-negative strains revealed that a loss-of-function mutation in GCR2 was responsible for the pho13-negative phenotype. Gcr2 is a global transcriptional factor involved in glucose metabolism. The results of RNA-seq confirmed that the deletion of GCR2 (gcr2) led to the upregulation of PPP genes as well as downregulation of glycolytic genes, and changes were more significant under xylose conditions than those under glucose conditions. Although there was no synergistic effect between pho13 and gcr2 in improving xylose fermentation, these results suggested that GCR2 is a novel knockout target in improving lignocellulosic ethanol production.